Professionalization and organizational problems of sports clubs: Is there a relationship? - Grazia Lang; Sarah Piller; Jürg Schmid; Markus Lamprecht; Siegfried Nagel (Bern Open Publishing, 2022)
Sports clubs have been reporting several organizational problems in recent decades (e.g., recruitment and retention of members and volunteers). At the same time, certain sports clubs have professionalized their strategies, structures, processes, and staff. However, previous research has not analyzed whether the professionalization of sports clubs is related to their organizational problems. Therefore, this study conducts, in the first step, a cluster analysis based on three dimensions of professionalization to identify professionalization types among sports clubs. In the second step, it examines differences in organizational problems among the identified professionalization types. The main findings are that (1) sports clubs with paid staff report fewer problems with recruiting and retaining members but more problems with finances than sports clubs that rely on voluntary work, and (2) sports clubs with increased professionalization of human resources management (HRM) and strategy have fewer problems with recruiting and retaining board members and coaches than sports clubs with low professionalization of HRM and strategy. These results show that professionalized sports clubs have different, but not necessarily fewer, organizational problems.